2018
DOI: 10.15240/tul/001/2018-1-002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mass layoffs on health insurance expenditures: the case of the Ostrava region

Abstract: Economics(see Šrám & Dostál, 2012) in a situation where the life expectancy for both men and women in the Moravian-Silesian Region is already below the nation-wide average (73.81 years for men and 79.99 for women in the Region in 2013, compared to the national average of 75. 91 and 80.80, respectively).The objective of the paper is to analyse the health status and health insurance expenditures for employees concerned by the AMO mass layoffs. The paper tests the hypothesis that closing down a large heavy indus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…As previous paragraphs show the complex relationship between the health and paid work the important relationship may be found also between health and unemployment. Among many others e. g. Louda et al (2018) in their study about effects of mass layoffs on health insurance expenditure found significant difference between the annual costs of treatment of employed (€ 536.8 a year) and unemployed persons (€ 705.4 a year) in their research sample from one of the region of Czech Republic. The difference of € 168.6 means that the costs of treating the unemployed are 31% higher than those for treating the employed, being higher than the relative increase in the risk of disease.…”
Section: Health and Workmentioning
confidence: 93%
“…As previous paragraphs show the complex relationship between the health and paid work the important relationship may be found also between health and unemployment. Among many others e. g. Louda et al (2018) in their study about effects of mass layoffs on health insurance expenditure found significant difference between the annual costs of treatment of employed (€ 536.8 a year) and unemployed persons (€ 705.4 a year) in their research sample from one of the region of Czech Republic. The difference of € 168.6 means that the costs of treating the unemployed are 31% higher than those for treating the employed, being higher than the relative increase in the risk of disease.…”
Section: Health and Workmentioning
confidence: 93%